Kemampuan Literasi Kimia Peserta Didik Sekolah Menengah Atas di kabupaten Gowa - Syamsidar Syamsidar; Suyanta Suyanta (Postgraduate, University of Mataram, 2024)
This research aims to describe chemical abilities in terms of content knowledge, chemical context, and higher-order learning skills of students on chemical equilibrium. This research is quantitative research with a survey method. The subjects of this research were students in six schools in Gowa Regency. The population in this study were all state high schools in Gowa Regency. The sampling technique is using random sampling after grouping schools based on accreditation. The instruments in this research were a chemical literacy ability test in the form of 20 multiple-choice objective questions. Chemists and chemical education experts carried out instrument validation. Empirical validation was carried out in class XI MIPA. The research results show that chemical literacy abilities in terms of content knowledge, chemical context, and higher-order learning skills are in the medium category.